Genetic analysis of traditional Ethiopian Highland Maize (Zea Mays L.) using molecular markers and morphological traits : implication for breeding and conservation - Myburg, Alexander Andrew (University of Pretoria, 2013)
Thesis (PhD (Genetics))--University of Pretoria, 2005.